PROSPECTS FOR THE DEVELOPMENT OF INCLUSIVE EDUCATION IN CHILDREN’S MUSIC AND ART SCHOOLS: LEGAL FOUNDATIONS, STATISTICAL INDICATORS, AND SOLUTIONS - Mamarasulov Xolmat Davronovich (Scholar Express Journal, 2025)
This article analyzes the current state and prospects for the development of inclusive education in Uzbekistan, particularly in children’s music and art schools. It examines the legal framework, statistical data, and pedagogical approaches to ensuring equal access to education for children with special needs. Based on national legislation and international data from UNICEF and the World Bank, the paper discusses the necessity of inclusive education in art institutions and the role of music in fostering social integration and emotional development. Practical experiences from Sherobod District’s music school are also presented, highlighting effective methods and challenges in the implementation of inclusive musical pedagogy
Keywords: inclusive education; children with special needs; national music